FEATURES OF THE COURSE OF THE WOUND PROCESS IN PATIENTS WITH DIABETIC FOOT SYNDROME - Prykhidko, R.A.; Krasnov, O.H.; Dudchenko, M.O.; Kravtsiv, M.I.; Zaiets, S.M.; Horodova-Andrieieva, T.V.; Krasnova, O.I. (World of Medicine and Biology, 2025)
The main cause of amputations in diabetes mellitus is an infectious-necrotic process on the foot. The aim of the study was to investigate the features of the wound process in patients with diabetic foot syndrome. 56 patients with purulent surgical pathology were examined. The main group consisted of patients with diabetes. The control group consisted of patients without diabetes with purulent pathology of the lower extremities. The clinical picture of the wound process, cytological changes and pH were studied. Patients with diabetes are characterized by early acidosis with a severe course of the wound process, and fluctuations in wound pH led to a change in the cytological picture. Such patients have a protracted first phase of the wound process, frequent complications. In severe cases, the wound process in patients with diabetes mellitus is polyphasic-discordinated, with several phases of the wound process.